The Migmatite and Gneisses in the Basement Complex of Southwestern Nigeria: a re-appraisal of their structural, mineralogical, and geochemical diversity - Obasi, Romanus, A.; Oluwatoyin, O. Akinola (IJRDO-Journal of Applied Science, 2020)
The structural, mineralogical and petrochemical diversity of migmatite-gneiss in the Basement complex of Southwestern Nigeria were re-appraised. The study of these country rocks exhibited structural heterogeneities that classified them into migmatite, banded gneiss and granite gneiss sub-groups. The units are typically hypidiomorphic to porphyroblastic with varying degrees of structural complexities. The variably deformed rocks have dominant N-S and NNE-SSW trending foliations and lineaments. These typically low-lying rocks are leucocratic to melanocratic and contain varying proportions of felsic-mafic components. Mineralogical composition shows dominance of quartz, feldspars, biotite, hornblende, and muscovite while opaque and pyroxene occur in subordinate amounts. Analytical results indicate that the rocks show cryptic but systematic variation in major elements distribution. The average mean SiO2 contents in Idanre migmatite (65.00 %), Ita-Ogbolu banded gneiss (62.53 %) and Ado-Ekiti granite gneiss (61.01 %) are suggestive of siliceous class while their average alkali (Na2O+K2O) contents showed 6.49 %, 9.23 %, and 8.52 % respectively. Variation plots of Na2O/Al2O3 versus K2O/Al2O3 indicate that the rocks have igneous parentage, Al2O3 versus MgO classifies the rocks as orthogneiss, K2O versus SiO2 diagram classifies them as continental granophyre. Trace element composition show lithophile elements (Ba, Rb, Sr, Zr and Ce) enrichment. Geochemical plot of Na2O/Al2O3 versus K2O/Al2O3 revealed these gneisses are products of anatexis of igneous protolith.